Psychosocial and health changes with bariatric surgery : a longitudinal study - Silva, Susana Sofia P. (2011)
Bariatric surgery is a treatment for morbid obesity associated with short term psychological and health improvements. Our study pretends to characterize current functioning, including coping and personality psychopathology and health problems in obese before surgery, six and 12 months follow-up. The results show that there was a significant weight loss reduction and a decrease on health problems and complaints on the 30 morbid obese participants in the six and 12 months follow-up. Psychopathology was not prevalent and there were no differences overtime. Neuroticism didn’t change but conscientiousness, extraversion and agreeableness increased. There was a decrease in general coping strategies, a mix of adequate and inadequate strategies. These results should be taken into account in evaluation and intervention with bariatric surgery candidates, promoting lifestyle changes namely their empowerment and coping strategies, thus contributing to treatment success.